A Case Study on the Origin of Near‐Earth Plasma. Issue 11 (31st October 2020) - Glocer, A.; Welling, D.; Chappell, C. R.; Toth, G.; Fok, M.‐C.; Komar, C.; Kang, S.‐B.; Buzulukova, N.; Ferradas, C.; Bingham, S.; Mouikis, C.
Abstract: This study presents simulations of the coupled space environment during a geomagnetic storm that separates the different sources of near‐Earth plasma. These simulations include separate fluids for solar wind and ionospheric protons, ionospheric oxygen, and the plasmasphere. Additionally, they include the effects of both a hot ring current population and a cold plasmaspheric population simultaneously for a geomagnetic storm. The modeled ring current population represents the solution of bounce‐averaged kinetic solution; the core plasmaspheric model assumes a fixed temperature of 1 eV and constant pressure along the field line. We find that during the storm, ionospheric protons can be a major contributor to the plasmasheet and ring current and that ionospheric plasma can largely displace solar wind protons in much of the magnetosphere under certain conditions. Indeed, the ionospheric source of plasma cannot be ignored. Significant hemispheric asymmetry is found between the outflow calculated in the summer and winter hemispheres, consistent with past observations. That asymmetric outflow is found to lead to asymmetric filling of the lobes, with the northern (summer) lobe receiving more outflow that has a higher proportion of O + and the southern (winter) lobe receiving less outflow with a higher proportion of H + . We moreover find that the inclusion of the plasmasphere can have a system‐wide impact. Specifically, when the plasmasphere drainage plume reaches the magnetopause, it can reduce the reconnection rate, suppress ionospheric outflow and change its composition, change the composition in the magnetosphere, and reduce the ring current intensity. Key Points: Ionospheric H + is a critically important contributor to the magnetosphere during a storm Seasonal effect on outflow create asymmetric filling of the lobes The inclusion of an additional plasmaspheric fluid has system‐wide effects